The Economic Costs of Noncommunicable Diseases in the Pacific Islands : A Rapid Stocktake of the Situation in Samoa, Tonga, and Vanuatu - World Bank (Washington, DC, 2017)
There are three main messages running throughout this report. First, Non Communicable Diseases (NCDs) can impose large health, financial and economic costs on countries. This is particularly important in the Pacific where Government already finances, and provides, the bulk of health services. Second, risk factors in the Pacific are feeding a pipeline of potentially expensive to treat NCDs, including diabetes and heart disease, but governments are already fiscally constrained in how much more they can provide to the health system. Third, from public health and public finance perspective, many of the NCDs are avoidable, or their health and financial costs can at least be postponed, through good primary and secondary prevention. This will require a more coherent approach to health system financing, and health system operations more generally.